Investigation of the Inherent Variability of the Mediterranean Sea Under Contrasting Extreme Climatic Conditions - Angeliki Sampatakaki; Vassilis Zervakis; Ioannis Mamoutos; Elina Tragou; Alexandra Gogou; Maria Triantaphyllou; Nikolaos Skliris (Frontiers in Marine Science, 2021)
The internal variability of the thermohaline circulation of the Mediterranean Sea is examined under contrasting extreme thermal and mass atmospheric forcing conditions. Three millennium-long numerical simulation experiments were performed under: (a) the current climatology, (b) a strong buoyancy forcing (SBF) scenario due to cold and dry conditions resembling the Younger Dryas event, and (c) a weak buoyancy forcing (WBF) scenario due to S1a sapropel deposition-like conditions (warm and wet). To isolate the inherent variability of the system, independent of interannual atmospheric forcing variability, the latter was defined as a perpetual year pertinent to each experiment. Self-diagnosed heat and salt fluxes, consistent to sea-surface characteristics of the above periods, forced three millenium-long, relaxation-free numerical experiments. These simulations were preceded by initial spin-up periods. The inherent spatiotemporal variability of the Mediterranean Sea was analyzed using the empirical orthogonal function (EOF) and spectral analysis on the simulated density fields. Our results revealed that the Mediterranean Sea exhibits high sensitivity to climatic conditions, allowing its circulation to change from anti-estuarine (for the SBF scenario, leading to a buoyancy loss to the atmosphere) to estuarine (for the WBF scenario, corresponding to a buoyancy gain from the atmosphere). In all three experiments, the interannual and decennial variabilities dominate in upper layers, and the decennial variability dominates in the Gibraltar and Sicily Straits. Under current climatic conditions the first two EOF modes express only 60% of the density variability in the deep layers. This contribution exceeds 90% under more extreme conditions. Moreover, the first EOF modes correspond to a basin-wide in-phase variability of the deep layers under the reference and WBF conditions. During SBF conditions the first modes reveal a vertical buoyancy exchange between upper and deeper layers. The second EOF mode of deep waters under both extreme scenarios showed that the western and eastern basins exchange buoyancy in decennial (for the cold/dry) and interdecennial (for the warm/humid) timescales. The residence time of the Eastern Mediterranean deep water was diagnosed to be centennial, semicentennial, and intercentennial for the cases of current period, SBF, and WBF, respectively.